Gender and Borrowing: A Comparative Analysis of English Loanword Use by Male and Female Hosts in Urdu Talk Shows - Saleem, Malaika; Ahmad, Ali (Regional Lens, 2025)
This paper explores the gender aspect of the occurrence of English loanwords in the Urdu political talk shows with respect to the language used by male and female presenters. Based on the theory of gender performativity proposed by Butler (1990), focusing on the Conversation Analysis (Sacks et al., 1974), the research focuses on the issue of how loanwords are used as the markers of power, identity, and professional positioning in the Pakistani press. Ten talk-show episodes (Five male-hosted and Five female-hosted) were transcribed using purposive sampling and analysed concerning lexical borrowing patterns, turn taking, interruptions and interactional behavior patterns. The results show evident gendered differences: male hosts use English loanwords to show power, to occupy more space than the interlocutor, and to strengthen the confrontational style of interviews, but female hosts strategically use it to demonstrate professionalism, sophistication, and modernity and to observe the culture-specific politeness and cooperative speech. This research combines sociolinguistics, gender studies and media discourse and thereby bridges a major gap in the knowledge about how linguistic borrowing creates gendered identities and is also a duplication of power structures within Pakistani broadcast journalism.